2014
DOI: 10.1111/ecog.00979
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore damage increases avian and ant predation of caterpillars on trees along a complete elevational forest gradient in Papua New Guinea

Abstract: Signals given off by plants to alert predators to herbivore attack may provide exciting examples of coevolution among organisms from multiple trophic levels. We examined whether signals from mechanically damaged trees (simulating damage by herbivores) attract predators of insects along a complete elevational rainforest gradient in tropical region, where various predators are expected to occur at particular elevational belts. We studied predation of artificial caterpillars on trees with and without ‘herbivorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
130
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(153 citation statements)
references
References 55 publications
18
130
1
1
Order By: Relevance
“…For example, studies in both tropical and temperate mountains have found increasing elevation to be associated with lower insect herbivore attack by parasitoids (Preszler andBoecklen 1996, Maunsell et al 2015), predatory arthropods (Koptur 1985, Rodríguez-Castañeda et al 2011, Rasmann et al 2014c, Sam et al 2015, Roslin et al 2017, and insectivorous birds (Sam et al 2015) (Fig. 1A).…”
Section: Tritrophic Interactions Influence Plant-insect Herbivore Elementioning
confidence: 98%
See 2 more Smart Citations
“…For example, studies in both tropical and temperate mountains have found increasing elevation to be associated with lower insect herbivore attack by parasitoids (Preszler andBoecklen 1996, Maunsell et al 2015), predatory arthropods (Koptur 1985, Rodríguez-Castañeda et al 2011, Rasmann et al 2014c, Sam et al 2015, Roslin et al 2017, and insectivorous birds (Sam et al 2015) (Fig. 1A).…”
Section: Tritrophic Interactions Influence Plant-insect Herbivore Elementioning
confidence: 98%
“…Recent work has also pointed at the importance of considering changes in predator species or guild composition (e.g. increasing bird predation but decreasing ant predation with elevation; Sam et al 2015), which may lead to contrasting elevational gradients in plant traits mediating indirect defence assuming that different predators select upon different traits.…”
Section: Tritrophic Interactions Influence Plant-insect Herbivore Elementioning
confidence: 99%
See 1 more Smart Citation
“…The use of ants as indicator species for monitoring, however, requires a caveat from an ecological and conservation point of view as they were restricted largely to low and mid-elevational zones. Predation pressure exerted from ants was observed to decline with increasing elevation within our study location ) and elsewhere (Sam et al 2015) due to decline not only in species richness but total abundance of ants at high elevations. In Lamington National Park, there are many regional and local endemic species that are restricted to the 1100-m elevational zone, including plant (e.g.…”
Section: Elevational Indicator Speciesmentioning
confidence: 49%
“…Brehm & Fiedler 2003;Kitching et al 2011;Sam et al 2015). Brehm & Fiedler 2003;Kitching et al 2011;Sam et al 2015).…”
Section: Introductionunclassified